A field study on providing standards for identification and problems encountered practice in earthquake deaths: İskenderun example - Demirci, İsmail Mehmet and Alptekin, Türker (The Bulletin of Legal Medicine, 2025)
Investigations conducted by the İskenderun Chief Public Prosecutor’s Office following this earthquake will identify the deaths listed in relevant sections of Code of Criminal Procedure No. 5271 and conduct forensic examinations and autopsies. This study will contribute to standardizing the identification, examination, and autopsy procedures that will be conducted as a result of the earthquake. This study examines in detail the step-by-step process followed during the postmortem examination procedures for who died in the earthquake that occurred in the İskenderun district on February 6, 2023. This step-by-step process serves as a preliminary study for future studies. There were primarily templates in this study and the final forms obtained from the identification and postmortem examinations were evaluated and shared for ease of use in disasters involving mass casualties. Following this fieldwork and observation, we believe that a planned effort must be undertaken by relevant institutions and organizations to identify those who died due to natural disasters and to ensure the proper conduct of the examination. We believe that pre-prepared reports or forms should be used to facilitate rapid and effective conduct of these procedures. For bodies whose identities cannot be determined, forensic examinations should be conducted using coding. Taking blood samples, fingerprints, and adequate photographs from dead bodies are not only important for identification but also necessary for subsequent criminal, legal, and administrative procedures. We believe next or developed forms by judicial bodies and relevant public institutions and organizations, could be helpful in combating potential future natural disasters.